Dari Kekosongan ke Kehidupan: Perspektif Islam Tentang Proses Kejadian Alam Semesta - Haikal, Muhammad; Amin, Faruq; Salma, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article reviews the Islamic view of how the universe was created, both from a theological and philosophical perspective. Using qualitative research methods and literature study, the author analyzes verses in the Qur’an related to the formation of the universe as well as philosophical thoughts of Muslim figures such as Al-Farabi, Ibn Sina, and Ibn Maskawaih. In the Islamic context, the creation of the universe is understood as evidence of God’s greatness exercised gradually and fully in wisdom. The philosophers’ concept of emanation also provides important insights into understanding the interaction between God and created beings. The article also emphasizes the relationship between science and the Quran in explaining the origin of the universe as well as encouraging the merger between revelation and rationality in scientific research. The results of this article show that Islam not only affirms a spiritual understanding of the universe, but also provides a space for scientific study regarding God’s creation.